Neoadjuvant‐modified FOLFIRINOX vs nab‐paclitaxel plus gemcitabine for borderline resectable or locally advanced pancreatic cancer patients who achieved surgical resection - Adam R. Wolfe; Dhivya Prabhakar; Vedat O. Yildiz; Jordan M. Cloyd; Mary Dillhoff; Laith Abushahin; Dayssy Alexandra Diaz; Eric D. Miller; Wei Chen; Wendy L. Frankel; Anne Noonan; Terence M. Williams (Cancer Medicine, 2020)
Abstract We conducted an institutional study to compare the clinical and pathological efficacy between the neoadjuvant therapy (NAT)‐modified FOLFIRINOX (mFOLF) vs nanoparticle albumin–bound paclitaxel plus gemcitabine (nab‐P/G) for borderline resectable pancreatic cancer (BRPC) and locally advanced pancreatic cancer (LAPC) patients who completed resection. The study retrospectively enrolled patients with pathologically confirmed BRPC or LAPC from 2010 to 2018 at our institution. The survival rates were determined by the Kaplan‐Meier method and log‐rank test was used to test differences. Cox's proportional hazard model was used to assess survival with respect to covariates. Seventy‐two patients who completed at least two cycles of neoadjuvant chemotherapy and surgical resection were included, with 52 (72.2%) patients receiving mFOLF and 20 (27.8%) receiving nab‐P/G. Patients treated with mFOLF had statistically higher rates of RECIST 1.1 partial or complete response (16/52 vs 1/20, P = .028). Additionally, mFOLF patients had greater pathological tumor size reduction, fewer positive lymph nodes, and higher treatment response grade compared to the nab‐P/G patients (all P < .05). The median overall survival was 33.3 months vs 27.1 months (P = .105), and distant metastasis‒free survival (DMFS) was 21.3 months vs 14.6 months (P = .042) in the mFOLF vs nab‐P/G groups, respectively. On multivariate analysis, mFOLF (hazard ratio, 0.428; 95% confidence interval [CI], 0.186‐0.987) and abnormal postoperative CA 19‐9 (hazard ratio, 2.47; 95% CI, 1.06‐5.76) were associated with DMFS. Among patients with BRPC and LAPC who complete surgical resection, neoadjuvant mFOLF was associated with improved pathological and clinical outcomes compared with nab‐P/G.